Games in Foreign Language Classroom - Milatovic, Biljana (Richtmann Publishing, 2012)
The aim of this paper is to point out some of the advantages of using games as accompanying elements of everyforeign language class. Games should be the integral part, be specific with respect to various aspects of learning, be directed tothe creation of the linguistic and communicative competence, should take into account the representation off all skills in theusage of language. Games make all tasks relaxed and quite easy, make students feel lively and vivacious, what is more thanwelcome, especially with young learners. They also create fantastic conditions and positive clamour what induce everyone totake part in and try to win.